التكنولوجية التعليمية وأهميتها فى دراسة اللغة العربية: EDUCATIONAL TECHNOLOGY AND ITS IMPORTANCE IN STUDY OF ARABIC LANGUAGE - Zainuddin, Darwin (El-Jaudah : Jurnal Pendidikan Bahasa dan Sastra Arab, 2020)
The present and future teaching of Arabic in Indonesia which is carried out in religious schools and colleges no longer allows classical language learning and does not help them to quickly speak and increase their interest in learning it. The most important thing to pay attention to is the application and reproduction of exercises with a focus on the use of modern teaching technology which should emphasize the methodology, curriculum, materials, and teaching tools. In the second world war, America invented this method to conduct training and prepare thousands of soldiers to learn world languages, and they found a systematic program by learning language independently through the auditory and visual systems. Modern teaching technology is the most important factor to implement by paying attention to students, teacher competence, and language environment so that they can be independent and teachers only act as supervisors when they learn Arabic. مفتاح الكلمة : تعليم , تكنولوجية , وسائل, اللغة العربية